Adaptation of aerobic training essentially involved autophagy, mitochondrial marker and muscle fibre genetic modulation in rat cardiac muscles. Issue 6 (15th November 2019) - Gunadi, Julia Windi; Tarawan, Vita Murniati; Setiawan, Iwan; Goenawan, Hanna; Ratnawati, Hana; Limyati, Yenni; Adhika, Oeij Anindita; Santoso, Andreas Wardono; Lesmana, Ronny; Supratman, Unang
Abstract: Information about the role of moderate acute treadmill training in modulating autophagy and mitochondrial markers that might be correlated with alteration of muscle fibre gene expression in rat cardiac muscles is very limited. In this present study, the researchers divided twenty male Wistar rats into four groups: sedentary control, 3, 6 and 15 days and subjected them to treadmill training with moderate intensity (20 m/min), 30 min each day. RNA was extracted from cardiac muscles and stored in temperature of −80°C. Specific primers were utilized for semi‐quantitative PCR. Treadmill training decreased autophagy‐related gene expression (LC3, p62) and upper stream signalling of autophagy (PIK3CA, Akt and mTOR) in 3 and 6 d, but stimulated gene expression of mitochondrial markers (PGC1α, Cox1, Cox2 and Cox4) in 15 days. αMHC gene expression increased while βMHC gene expression decreased in 15 days. In line with this, autophagy‐related genes increased in 3 and 6 days and returned to baseline in 15 days. The increment in mitochondrial gene expression might be correlated with shifting gene expression of αMHC and βMHC in 15 days. Taken together, acute adaptation in cardiac muscles is stimulated by genetic modulation of autophagy, mitochondrial marker and muscle fibre that may explain physiological cardiac adaptation after training. This study can be used as a reference for optimizing performance in period of cardiac muscle adaptation stimulated by treadmill training.